2018
DOI: 10.3390/su10072377
|View full text |Cite
|
Sign up to set email alerts
|

Usage Behaviour of Public Spaces Associated with Sport and Recreational Activities

Abstract: Public spaces (PS) encourage personal interaction and promote behaviours such as doing sport and recreational activities. This study analysed the characteristics of sport and recreational activities among the adult population of Seville associated with and/or determining the use of a PS for the activity. We adopted a cross sectional survey design with 1002 subjects (18+) from the municipality of Seville using a questionnaire on habits of sport and recreational activities. We then performed a descriptive, corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The rate of physical activity in children attending schools that provide proper quality sports facilities is definitely higher; also, where students are required to spend time in the open air where they can use part of the infrastructure without being attended to, the rate of physically active children is even higher [ 54 ]. It has been observed in several parts of the world that an increasing proportion of the population has been doing physical exercises in multi-purpose community spaces like parks or public squares [ 55 ]. Therefore, urban planning should also focus on developing these spaces in such a way so that they would be suitable for physical activities and are easily accessible for the population at the same time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of physical activity in children attending schools that provide proper quality sports facilities is definitely higher; also, where students are required to spend time in the open air where they can use part of the infrastructure without being attended to, the rate of physically active children is even higher [ 54 ]. It has been observed in several parts of the world that an increasing proportion of the population has been doing physical exercises in multi-purpose community spaces like parks or public squares [ 55 ]. Therefore, urban planning should also focus on developing these spaces in such a way so that they would be suitable for physical activities and are easily accessible for the population at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…When sports facilities are eye-catching in a given neighborhood, residents will be more willing to play some sport simply due to the visual stimulus [ 33 ]. An increasing proportion of residents do exercises in multi-purpose community places, parks, or public squares [ 55 ]. Residents’ physical activity is also influenced by the availability or lack of transportation infrastructure and facilities [ 39 , 75 , 76 , 77 , 78 , 79 , 80 , 142 , 143 ].…”
Section: Discussionmentioning
confidence: 99%
“…The industry perception includes the perceptions of sports brand, skills training, service personnel, internet consulting, establishing industry base, insurance market, and stimulate consumption [4]. Past studies have demonstrated that the perception of public space has an effect on people's physical activity [11,16]. Thus, the space perception of RS should include perceptions of community sports space, road side, grass space, city parks, residences surrounding, and sports parks.…”
Section: Measure For Data Collectionmentioning
confidence: 99%
“…The RS industry is comprised of companies engaging in a diversity of activities, from the manufacturing of RS goods, provision of RS services, media, to the construction of RS facilities [11]. In recent years, some researchers have focused on the study of the RS industry [4].…”
Section: Introductionmentioning
confidence: 99%
“…The use of social media for sport and exercise-related purposes prompts sporting activities in the physical environment and vice versa [12]. Therefore, sport and exercise-related activities carried out on social media platforms can provide rich information regarding places, the use of space, and people's experiences of landscape [15,43,44,98]. However, there is a lack of in-depth quantitative studies of sport and exercise-related activities in the literature using social media messages as a source of data.…”
Section: Urban Places and User-generated Contentmentioning
confidence: 99%